Driving Global Expansion: Exploring the Impact of Digital Marketing, Financial Management, and Financial Literacy on the Export Performance of Wood Processing SMEs - Oktora, Yekie Senja; Sudarmiatin; Bidin, Rosmiza (MSJ : Majority Science Journal, 2024)
This research aims to investigate the dynamics of internationalization among wood processing SMEs, examining the relationship between digital marketing strategies (X1), financial management practices (X2), financial literacy (X3), and export performance. With globalization reshaping markets, SMEs engaged in wood processing face opportunities and challenges in entering global markets. Through a mixed-methods approach, including quantitative analysis and interviews with industry experts, this study delves into the mechanisms through which digital marketing initiatives, effective financial management, and increased financial literacy contribute to the export success of wood processing SMEs. The research population includes wood processing SMEs actively involved in export, while the sample is purposively selected. Samples of this research are 136 MSMEs.Data were obtained through structured surveys and in-depth interviews with industry stakeholders. Data analysis techniques include regression analysis to test the relationship between independent variables (X1, X2, and X3) and the dependent variable (export performance). The findings indicate that digital marketing practices, effective financial management, and high financial literacy significantly contribute to enhancing the export performance of wood processing SMEs, with practical implications for the development of better strategies in facing global markets.